Production of activated carbon using Musa Acuminata - Nurhusna Fuad (Penerbit Universiti Malaysia Perlis, 2010)
The sorption of acid orange 7 dyes from aqueous solution by banana stalk, an abundant agricultural waste in Malaysia was studied in a batch system with respect to contact time and activated carbon dosage. Sorption isotherm of acid orange 7 dyes onto banana stalk was determined at room temperature with initial concentration of 250ppm and neutral condition of pH 7. The mixture was agitated at 200 rpm using orbital shaker and concentration of acid orange 7 dyes were analyzed using UV spectrophotometer. Activated carbon was sieved to 1.0- 1.25mm in size and chemically activated using sulfuric acid (1 mol). The optimum dosage was remarkable at 1.4 with percentage removal of 98.0%. Adsorption achieved equilibrium state at 2 hours contact time. The equilibrium isotherm data were analyzed using two isotherm models which are Langmuir and Freundlich model to determine the best fit equation for the sorption of acid orange 7 dyes on banana stalk.